2002
DOI: 10.1002/jmv.2149
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infection in haemodialysis patients: A case‐control study in Saudi Arabia

Abstract: To determine the prevalence of antibody to hepatitis E virus (IgM anti-HEV) among haemodialysis patients and evaluate whether there was an increased risk of infection and exposure to HEV in an area of endemic viral hepatitis, serum samples obtained from 83 Saudi patients on chronic haemodialysis (group 1), 400 sex- and age-matched healthy subjects (group 2) and hospital patients (group 3) were tested for the IgM anti-HEV and IgG anti-HEV. The prevalence of anti-HEV among the patients (group 1) and the healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 24 publications
3
51
1
3
Order By: Relevance
“…However, another study did not support this hypothesis (14). In addition, transmission of HEV infection from prenatal transmission was reported in some studies (15)(16)(17). Some studies in Iran indicated a higher transmission rate of HEV infection among injection drug users (IDUs) and hemodialysis patients than the general population (18-23).…”
Section: Introductionmentioning
confidence: 99%
“…However, another study did not support this hypothesis (14). In addition, transmission of HEV infection from prenatal transmission was reported in some studies (15)(16)(17). Some studies in Iran indicated a higher transmission rate of HEV infection among injection drug users (IDUs) and hemodialysis patients than the general population (18-23).…”
Section: Introductionmentioning
confidence: 99%
“…Başlıca fekal-oral yolla bulaşan, parenteral ve vertikal yolla da bulaşabileceği bildirilen hepatit E virüsünün prevalansının da hemodiyaliz hastalarında normal popülasyondan daha yüksek olduğu bildirilmiştir [8][9][10][11].…”
Section: Discussionunclassified
“…Hemodiyaliz hastalarında hepatite neden olan hepatit E (HEV), Hepatit G (HGV) , transfüzyonla bulaşan virus (TTV) viruslerinin sıklığına ilişkin çeşitli çalışmalar yapılmıştır ve Transfusion transmitted virus (TTV)'un bulaş yolu tam olarak aydınlatılamasa da, hemodiyaliz hastalarında TTV seroprevalansı %9,3-83 arasında değişmektedir [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…HEV transmission has been reported in a hemodialysis unit 34 and a hematology ward. 35 Hence, we wondered whether nosocomial HEV transmission could occur in organ transplant recipients who have frequent hospitalizations, especially within the early post-transplant period.…”
Section: Mode Of Hev Transmission Among Patients With a Sotmentioning
confidence: 99%